Examining the Mediating Role of Self-Concept in the Relationship between Object Relations and Narcissistic Personality - Gholami Zarch, Morteza; Taghvaei, Davood; Pirani, Zabihollah (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to examine the mediating role of self-concept in the relationship between object relations and narcissistic personality.Methods and Materials: This research was descriptive and conducted using a correlational method. The statistical population included all students studying at universities in the city of Qom during the academic year 2020-2021, from which 397 individuals were selected using convenience sampling. Participants completed questionnaires on narcissistic personality, object relations, and self-concept scales. Structural equation modeling was performed using data obtained from the questionnaires.Findings: The results indicated that object relations directly explained 63% and indirectly through self-concept explained 25% of the variance in narcissistic personality. Overall, the estimated structural model, where object relations were the predictor variable and self-concept was the mediating variable, explained 88% of the variance in narcissistic personality.Conclusion: Therefore, it can be concluded that narcissistic personality is explained both directly and indirectly through self-concept by object relations.